Peran Kompetensi Pedagogik Guru dalam Meningkatkan Kualitas Pembelajaran Fikih di MA Al-Husaini Pegantenan - Sunu, Sunu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to understand the role of teacher competency in improving the quality of learning in the subject of Fiqh. This study was conducted at MA Al-Husaini Pegantenan. The approach used in this research is a qualitative approach with a type of field research. The data collection process was carried out through interviews, observations, and documentation. The data obtained were analyzed qualitatively with the stages of: (1) data reduction, (2) data presentation, and (3) conclusion drawing. The results of the research found that teachers of the Fiqh subject have taken the procedural steps and processes that should be in designing Fiqh learning. This can be seen in the findings of documents in the form of prota, promissory notes, syllabus and lesson plans. The learning process is carried out through three stages, namely introduction, core activities and closing. The approach taken is active learning and multimedia-based learning, in teacher learning provides sufficient space for students to develop their creativity. To find out the success of learning the teacher conducts authentic assessments of both cognitive, affective and psychomotor.